2021
DOI: 10.1002/qj.3961
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution in the Gobi Desert region: Analysis of dust‐storm events

Abstract: Air pollutants in nine cities of the Gobi Desert region are examined in this study. Mean concentrations of PM2.5 and PM10, retrieved from ground‐based air quality monitoring stations, were 36.2 ± 23.7 and 97.3 ± 84.5 μg·m−3, respectively. The highest concentrations of pollutants were in spring and winter. This can be explained by wind‐borne dust in the spring and emissions from domestic sources during the winter heating season. The highest PM2.5 and PM10 concentrations were registered in a period of dust‐storm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…A dust storm is a dry deposition with amounts of aerosolized dust in the atmosphere which arises from desert areas (Choi & Zhang, 2008). Airborne dust can dramatically reduce visibility and air quality, and cause respiratory and circulatory system diseases (Degobbi et al., 2011; Filonchyk et al., 2021; Hasunuma et al., 2021; Huang, 2013). Dust particles can be transported from its original place to other areas through wind transport and influence on solar radiation balance and cloud formation (Huang, 2013; Huang et al., 2014; Kim et al., 2016; Uno et al., 2001; W. Wang et al., 2010; Yang et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A dust storm is a dry deposition with amounts of aerosolized dust in the atmosphere which arises from desert areas (Choi & Zhang, 2008). Airborne dust can dramatically reduce visibility and air quality, and cause respiratory and circulatory system diseases (Degobbi et al., 2011; Filonchyk et al., 2021; Hasunuma et al., 2021; Huang, 2013). Dust particles can be transported from its original place to other areas through wind transport and influence on solar radiation balance and cloud formation (Huang, 2013; Huang et al., 2014; Kim et al., 2016; Uno et al., 2001; W. Wang et al., 2010; Yang et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The volume concentration dropped to 0.43 µm 3 µm −2 on 12 April. Similar to the volume size distribution of a dust event occurring in Beijing, the volume concentration at the peak radius was 1.12-0.92 µm 3 µm −2 [64]. SSA is the ratio of aerosol scattering coefficient to extinction coefficient, which is an important optical parameter to measure the radiative forcing of aerosols and reflects the scattering and absorption characteristics of aerosols [65].…”
Section: Optical and Microphysical Properties Of Aerosol In The Dust ...mentioning
confidence: 85%
“…The Middle East and Southwest Asia also exhibited a large SSA (0.99) during dust periods; however, it is possible that changes and the heating effect of dust aerosol in the atmosphere was significant. It was found that the ARFATM was 125.55 W/m 2 during the dust day in the Gobi Desert [64]; the ARFATM during two dust storms in the Indo-Gangetic basin were 124 W/m 2 and 84 W/m 2 , respectively [71]. Above all, dust aerosol can significantly affect SSA and radiative forcing and have an important influence on the regional climate and atmospheric circulation [26].…”
Section: Optical and Microphysical Properties Of Aerosol In The Dust ...mentioning
confidence: 99%
“…Intensity of dust storms facilitates the desertification process by transporting and depositing sediments, resulting in loss of crops, damaged infrastructure and uninhabitable environment (Fernandes et al, 2019, Fernández et al, 2019, Eshghizadeh and Environment, 2021, Rashki et al, 2021. They play an important role in amplifying climate change process (Xie et al, 2010, Karimi et al, 2012 their radiative properties are of special significance due to their duel role in heating and cooling affect of radiation (Rezaei et al, 2019, Filonchyk et al, 2021. Over deserts, air borne dust creates a cooling effect day time; by absorbing terrestrial and cosmic radiation, the effect is reversed at night due to the increased downward energy flux, hence cause a change in earth's energy budget (Prakash et al, 2014, Francis et al, 2022.…”
Section: Introductionmentioning
confidence: 99%